Вплив специфічного акцизу на розвиток ринку тютюнових виробів в Україні - Глущенко, Анастасія Костянтинівна; Фадєєва (Коптєва), Ганна Миколаївна (НТУ "ХПІ", 2017)
Проаналізовано вплив акцизного оподаткування на економічний та соціальний розвиток ринку тютюнових виробів в Україні. Запропоновано напрями реалізації акцизно ї політики щодо попередження шкідливих наслідків паління.

Excise tobacco taxation provides significant revenue because the tax burden on them is one of the largest among consumer products. However, the current amount of excise taxation differs significantly from the corresponding indicators in the leading EU countries. The analyzes the impact of the excise tax on economic and social development of the market of tobacco products in Ukraine. Directions implementation of excise policy for the prevention of the harmful effects of smoking. Thus, the data can be used in furt her research to a more detailed analysis of excise tobacco taxation and development forecasts of market development of the products.
Keywords: акцизний податок; акцизне оподаткування; адвалорний акциз; мінімальний акцизний податок; акцизне навантаження; excise tax; ad valorem excise tax; specific excise tax; minimum excise tax; excise burden; tobacco products